High Dielectric Tunability and Figure of Merit at Low Voltage in (001)-Oriented Epitaxial Tetragonal Pb0.52Zr0.48TiO3 Thin Films - Hongwang Li; Chao Liu; Jun Ouyang (Nanomaterials)
Ferroelectric thin films with a high dielectric tunability (η) have great potential in electrically tunable applications, including microwave tunable devices such as phase shifters, filters, delay lines, etc. Using a modified Landau–Devonshire type thermodynamic potential, we show that the dielectric tunability η of a (001) tetragonal ferroelectric film can be analytically solved. After a survey of materials, a large η value above 60% was predicted to be achievable in a (001)-oriented tetragonal Pb(Zr0.52Ti0.48)O3 (PZT) film. Experimentally, (001)-oriented PZT thin films were prepared on LaNiO3-coated (100) SrTiO3 substrates by using pulsed laser deposition (PLD). These films exhibited good dielectric tunability (η ~ 67.6%) measured at a small electric field E of ~250 kV/cm (corresponding to 5 volts for a 200 nm thick film). It only dropped down to ~54.2% when E was further reduced to 125 kV/cm (2.5 volts for 200 nm film). The measured dielectric tunability η as functions of the applied electric field E and measuring frequency f are discussed for a 500 nm thick PZT film, with the former well described by the theoretical η(E) curves and the latter showing a weak frequency dependence. These observations validate our integrated approach rooted in a theoretical understanding.